Genesis of Basalts of the Raohe Subduction–Accretion Complex in the Wandashan Block, NE China, and Its Inspirations for Evolution of the Paleo-Pacific Ocean - Qing Liu; Cui Liu; Jixu Liu; Jinfu Deng; Shipan Tian (Applied Sciences)
The Raohe subduction–accretion complex (RSAC) in the Wandashan Block, NE China, comprises ultramafic rocks, gabbro, mafic volcanic rocks, deep-sea and hemipelagic sediments, and trench–slope turbidites. We investigate the basalts within the RSAC to resolve debates on its origin. Zircon U-Pb dating of pillow basalt from Dadingzi Mountain yields a concordant age of 117.5 ± 2.1 Ma (MSWD = 3.6). Integrating previous studies, we identify three distinct basalt phases. The Late Triassic basalt (210 Ma–230 Ma) is characterized as komatites–melilitite, exhibiting features of island arc basalt, as well as some characteristics of E-MORB. It also contains high-magnesium lava, suggesting that it may be a product of a juvenile arc. The Middle Jurassic basalt (around 159 Ma–172 Ma) consists of a combination of basalt and magnesium andesite, displaying features of oceanic island basalt and mid-ocean ridge basalt. Considering the contemporaneous sedimentary rocks as hemipelagic continental slope deposits, it is inferred that these basalts were formed in an arc environment associated with oceanic subduction, likely as a result of subduction of the young oceanic crust. The Early Cretaceous basalt (around 117 Ma) occurs in pillow structures, exhibiting some characteristics of oceanic island basalt but also showing transitional features towards a continental arc. Considering the regional distribution of the rocks, it is inferred that this basalt likely formed in a back-arc basin. Integrating the formation ages, nature, and tectonic attributes of the various structural units within the RSAC, as well as previous research, it is inferred that subduction of the Paleo-Pacific Ocean had already begun during the Late Triassic and continued into the Early Cretaceous without cessation.